Innovative Logistics Practices for Sustainable Transportation - Drivers and Barriers - Gimeno Piquer, Sara; Teraphonghom, Nutcha (My University, 2013)
ABSTRACT This Master’s thesis has been conducted in collaboration within the section of Logistics and Transportation at Chalmers University of Technology in regards to Innovative Logistics Practices (ILP) and the features of the main projects on going across the European territory that respond to this term. Through exhaustive literature review, the specific characteristics of this type of supply chain practices have been classified and analysed in order to get a better understanding of the driver mechanisms surrounding them and what is to be done in the future to overcome existing barriers that tend to delay the implementation of these ventures. Four types of ILP have been drawn and analysed: e-Freight, co-modality, UFT and intralogistics. These types are contextualized in the different project ventures that deal with their type of ILP in order to identify specific drivers and barriers. A great amount of coincidences had been observed as common drivers and barriers that have been classified and discussed separately in order to better highlight the relevant aspects of each of them. Economic, social and environmental aspects can be drawn as the main responsible topics with a clear interaction with technology and stakeholders positions in the surveyed project. At Findings, the different drivers and barriers are analysed in a theoretical context with specific observations and recommendations for each type of related ILP. Last, a case study has been carried out in order to better asses which parameters affect the environmental advantages of co-modality, which are often regarded as the most environmental advantage. It true that economies of scale and the use of electricity entails a lower socio-environmental cost for transportation, different aspects of the transport scenarios are further discussed in order to debate critical points and the feasibility of co-modality in the future as socio-environmental competitive solution.
Keywords: Transport; Övrig industriell teknik och ekonomi; Transport; Other industrial engineering and economics